143k views
3 votes
-4k + 2(5k − 6) = −3k – 48

User Gordie
by
5.8k points

2 Answers

7 votes
so to answer your question i’m gonna have to say that the answer is 69.
User Vidalsasoon
by
5.6k points
0 votes

Answer:

k = -4

Explanation:

-4k + 2(5k − 6) = −3k – 48

Distribute on the left side.

-4k + 10k - 12 = -3k - 48

Combine like terms on the left side.

6k - 12 = -3k - 48

Add 3k to both sides.

9k - 12 = -48

Add 12 to both sides.

9k = -36

Divide both sides by 9.

k = -4

User Gugu
by
5.2k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.